Optimisation of a PC12 cell‑based in vitro stroke model for screening neuroprotective agents - Chua, Pin Fen; Lim, William Kiong Seng (Springer Nature Limited, 2021)
Stroke causes death and disability globally but no neuroprotectant is approved for post-stroke neuronal injury. Neuroprotective compounds can be identified using oxygen glucose deprivation (OGD) of neuronal cells as an in vitro stroke model. Nerve growth factor (NGF)-differrentiated PC12 pheochromocytoma cells are frequently used. However, investigators often find their clonal variant undiferentiable and are uncertain of optimal culture conditions. Hence we studied 3 commonly used PC12 variants: PC12 Adh, PC12 from Riken Cell Bank (PC12 Riken) and Neuroscreen-1 (NS-1) cells. We found DMEM the optimal media for PC12 Riken and NS-1 cells. Using a novel serum-free media approach, we identified collagen IV as the preferred adhesive substrate for both cell lines. We found PC12 Adh cells cannot attach without serum and is unable to diferentiate using NGF. NS-1 cells differentiated to a maximal 72.7 ± 5.2% %, with substantial basal differentiation. We optimised differentiated NS-1 cells for an in vitro stroke model using 3 h of OGD resulting in~ 70% viable cells. We screened 5 reported neuroprotectants and provide the frst report that serotonin is antiapoptotic in a stroke model and the 5-HT1A agonist 8-hydroxy-2-(di-n-propylamino) tetralin (8-OH-DPAT) is neuroprotective in PC12 cells. Thus we demonstrate the optimisation and validation for a PC12 cellbased in vitro stroke model.